HUMOR AND SATIRE IN SHAKESPEARE’S COMEDIES - Eshniyozova Jasmina Jo’rabekovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This topic provides a comprehensive analysis of William Shakespare's comedic works, examining their thematic and structural intricacies, as well as their socio-cultural contexts. It categorizes Shakespeare's comedies into distinct groups based on thematic elements such as setting and narrative style, highlighting the evolution of his comedic artistry over time. Furthermore, it delves into specific plays, such as "The Comedy of Errors" and "A Midsummer Night's Dream," offering insightful commentary on their themes, characters, and narrative techniques. Additionally, the annotation explores the interplay between comedy and tragedy in Shakespeare's works, showcasing his ability to navigate the complexities of human existence with wit and insight. Overall, this annotation serves as a valuable resource for scholars and enthusiasts alike, offering fresh perspectives on Shakespeare's enduring comedic legacy.